Molecular Detection of Associated Genes with The Highly Virulent Avian Pathogen Escherichia Coli Isolated from Chicken Fecal Samples - Sura J. Mohammed; Ali A. Al-Iedani (International Journal of Medical Toxicology and Legal Medicine, 2024)
Bird disease-causing E. coli (Avian colibacillosis), the most common disease-causing morbidity in poultry worldwide, is mainly caused by avian pathogenic E. coli (APEC). The present study aimed to detect virulence-associated genes of E. coli isolated from chickens of different origins in Basrah Province. 84 isolates were examined by Polymerase Chain Reaction for the existence of the five most related genes defined for avian colibacillosis (hlyF, ompT, iroN, iutA, and iss). The percent of genes related to the virulence of APEC found in isolates were: ISS (75%), ompT (60%), hlyF (45%), iroN (42%), and iutA (37%), however, 6% of the isolates had all five genes together. The antimicrobial susceptibility of all isolates to seven antibiotics (Ampicillin, Ciprofloxacin, Colistin, Gentamicin, Chloramphenicol, Cefotaxime, and Imipenem) was verified. The antimicrobial resistance of the isolates (98%) was detected to be resistant to ampicillin, ciprofloxacin (68%), cefotaxime (64%), colistin (61%), gentamicin (59%), chloramphenicol (42%) and imipenem (32%). Regarding the E. coli isolates contain all 5 genes linked with the highly virulent APEC, antibiotic susceptibility testing revealed that 5 (100%) of the isolates were resistant to ciprofloxacin and ampicillin, 80% of the isolates were resistant to colistin and gentamicin, and 40% of APEC isolates were resistant to cefotaxime; however, 20% were resistant to imipenem. In conclusion, only a few fecal E. coli isolated from chickens had genes associated with virulent APEC, and these isolates have high antibiotic resistance.